FOUR EYES PRINCIPLE DALAM PENGELOLAAN RISIKO KREDIT PADA BANK - Nurwahjuni Nurwahjuni; Abd Shomad (Yuridika, 2016)
In order to implement the four eyes principle in the provision of bank credit there should be a separation of functions between the analysis, approval, and credit administration. The separation of functions is done in order to secure the credits begin the loan process until the credits were disbursed, even banks should separate settlement function of problem loans with a function that decides lending. This is done in order to avoid any conflict of interest between a bank and its clients' interests debtors. Due to the four eyes principle applied in lending may cause a credit crunch. Problem loans will affect the profitability and solvency of banks that ends decrease the soundness of the bank. Bank may be subject to administrative sanctions and criminal sanctions when the Member of the Board of Commissioners, Board of Directors, or bank employees who deliberately do not implement the measures necessary to ensure adherence to the bank of the provisions of this Act and the provisions of other legislation applicable to banks.